Calycosin inhibits porcine reproductive and respiratory syndrome virus replication and activates RIG-I/IRF3 signaling pathway - Chang, Yafei; Li, Zhaopeng; Wang, Mengqi; Pei, Kanglei; Chang, Xiaobo; Ma, Jinyou (Frontiers in Veterinary Science, 2025)
Porcine reproductive and respiratory syndrome virus (PRRSV), the causative pathogen of PRRS, remains one of the most important pathogens threatening the global pig industry. Due to the genetic diversity of PRRSV, the existing commercially vaccines cannot completely protect pigs from PRRSV infection. Flavonoid compounds play an important role in inhibiting viral replication. In this study, we found that calycosin, a natural active compound isolated from astragalus, could inhibit PRRSV replication regardless of whether calycosin was added pre-, co-, or post-PRRSV infection in vitro. Furthermore, coincubation of calycosin with PRRSV showed a better inhibitory effect compared to separate incubation, and calycosin mainly inhibited virus replication, assembly and release stages. Importantly, calycosin enhanced the antiviral immunity, as shown by the increased expression of IFN-β and ISG56. Subsequently, we discovered that calycosin promoted the expression of RIG-I and MAVS, and induced the phosphorylation and nuclear translocation of IRF3 during PRRSV infection. Collectively, calycosin could markedly inhibit PRRSV replication and activate the RIG-I/IRF3 signaling pathway. These data contribute to understanding the role of calycosin in PRRSV replication, and may provide valuable insights for the development of future antiviral strategies.